Style and Classification in the History of Art - Matthew Martin (Journal of Art Historiography, 2011)
Review of: Robert Bagley, Max Loehr and the Study of Chinese Bronzes. Style and Classification in the History of Art, Ithaca, NY: Cornell East Asia Series, 2008. Robert Bagley’s monograph uses his mentor Max Loehr’s work on Shang period Chinese bronzes as the starting point for a critical examination of issues surrounding the art historical notion of ‘style’. Bagley critiques the tendency by much art history to the reification of ‘style’, an intellectual construction, and dismisses the idea that ‘style’ can somehow embody the characteristics of a ‘Zeitgeist’. Bagley argues for the independence of artistic and aesthetic concerns in explaining developments in the formal characteristics of objects of material culture, without the need to appeal to external forces such as literary sources or a symbolic system. We must take seriously, Bagley suggests, that visual effect, independent of other considerations, was a characteristic consciously pursued by artists of the past.